There's Circles Everywhere!

Geometry Level 3

Extend the diagram above to an infinite number of circles. For each integer n 1 n \geq 1 , circle w n w_{n} is tangent to w n 1 w_{n - 1} and tangent to the line y = x y = x and the positive x x -axis.

Let C n C_{n} and A n A_{n} be the circumference and the area of the n n th circle respectively. Find:

( n = 1 C n ) 2 n = 1 A n \dfrac{(\sum_{n = 1}^{\infty} C_{n})^2}{\sum_{n = 1}^{\infty} A_{n}}


The answer is 32.8375088952649884.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rocco Dalto
Jan 27, 2021

O w 0 = 4 + 2 2 R 1 \overline{Ow_{0}} = \sqrt{4 + 2\sqrt{2}}R_{1}

O A 1 w 0 w 1 A 2 w 0 4 + 2 2 R 1 R 1 = R 1 + R 2 R 1 R 2 \triangle{OA_{1}w_{0}} \sim \triangle{w_{1}A_{2}w_{0}} \implies \dfrac{\sqrt{4 + 2\sqrt{2}}R_{1}}{R_{1}} = \dfrac{R_{1} + R_{2}}{R_{1} - R_{2}} \implies

( 4 + 2 2 1 ) R 1 = ( 4 + 2 2 + 1 ) R 2 (\sqrt{4 + 2\sqrt{2}} - 1)R_{1} = (\sqrt{4 + 2\sqrt{2}} + 1)R_{2} \implies R 2 = 4 + 2 2 1 4 + 2 2 + 1 R 1 R_{2} = \dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1}R_{1}

R 3 = 4 + 2 2 1 4 + 2 2 + 1 R 2 = ( 4 + 2 2 1 4 + 2 2 + 1 ) 2 R 1 R_{3} = \dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1}R_{2} = (\dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1})^2R_{1}

In General: R n = ( 4 + 2 2 1 4 + 2 2 + 1 ) n 1 R 1 R_{n} = (\dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1})^{n - 1}R_{1}

A n = π R n 2 = π R 1 2 ( ( 4 + 2 2 1 4 + 2 2 + 1 ) 2 ) n 1 \implies A_{n} = \pi R_{n}^2 = \pi R_{1}^2((\dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1})^2)^{n - 1}

A = n = 1 A n = π R 1 2 n = 1 ( ( 4 + 2 2 1 4 + 2 2 + 1 ) 2 ) n 1 \implies A = \sum_{n = 1}^{\infty} A_{n} = \pi R_{1}^2\sum_{n = 1}^{\infty} ((\dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1})^2)^{n - 1}

= ( 4 + 2 2 + 1 ) 2 4 4 + 2 2 π R 1 2 = \dfrac{(\sqrt{4 + 2\sqrt{2}} + 1)^2}{4\sqrt{4 + 2\sqrt{2}}}\pi R_{1}^2

and

C n = 2 π R n = 2 π R 1 ( 4 + 2 2 1 4 + 2 2 + 1 ) n 1 C_{n} = 2\pi R_{n} = 2\pi R_{1}(\dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1})^{n - 1}

C = n = 1 C n = 2 π R 1 n = 1 ( 4 + 2 2 1 4 + 2 2 + 1 ) n 1 = \implies C = \sum_{n = 1}^{\infty} C_{n} = 2\pi R_{1}\sum_{n = 1}^{\infty} (\dfrac{\sqrt{4 + 2\sqrt{2}} - 1}{\sqrt{4 + 2\sqrt{2}} + 1})^{n - 1} =

( 4 + 2 2 ) π R 1 C 2 = ( 4 + 2 2 ) 2 π 2 R 1 2 (\sqrt{4 + 2\sqrt{2}}) \pi R_{1} \implies C^2 = (\sqrt{4 + 2\sqrt{2}})^2 \pi^2 R_{1}^2

C 2 A = 4 π 4 + 2 2 32.8375088952649884 \implies \dfrac{C^2}{A} = 4\pi\sqrt{4 + 2\sqrt{2}} \approx \boxed{32.8375088952649884} .

Chew-Seong Cheong
Jan 28, 2021

For any measure of O \angle O , as the pattern repeats, the ratio of the shortest distance of any circle (for example: O A = l 1 OA= l_1 ) to the apex O O and the diameter of the circle ( A B = d 1 AB=d_1 ) is a constant. Let the constant be k k then:

l 1 d 1 = l 2 d 2 = l 3 d 3 = = k \frac {l_1}{d_1} = \frac {l_2}{d_2} = \frac {l_3}{d_3} = \cdots = k

We note that:

l n 1 = d n + l n k d n 1 = d n + k d n d n = k 1 + k d n 1 r n = k 1 + k r n 1 = ( k 1 + k ) n 1 r 1 where r n = d n 2 , the radius of n th circle. \begin{aligned} l_{n-1} & = d_n + l_n \\ kd_{n-1} & = d_n + kd_n \\ d_n & = \frac k{1+k} d_{n-1} \\ \implies r_n & = \frac k{1+k} r_{n-1} = \left(\frac k{1+k} \right)^{n-1}r_1 & \small \blue{\text{where }r_n = \frac {d_n}2 \text{, the radius of }n\text{th circle.}} \end{aligned}

Then we have:

n = 1 C n = n = 1 2 π r n = n = 0 2 π ( k 1 + k ) n r 1 = 2 π r 1 1 k 1 + k = 2 π r 1 ( 1 + k ) n = 1 A n = n = 1 π r n 2 = π r 1 2 1 ( k 1 + k ) 2 = π r 1 2 ( 1 + k ) 2 1 + 2 k ( n = 1 C n ) 2 n = 1 A n = ( 2 π r 1 ( 1 + k ) ) 2 π r 1 2 ( 1 + k ) 2 1 + 2 k = 4 π ( 1 + 2 k ) \begin{aligned} \sum_{n=1}^\infty C_n & = \sum_{n=1}^\infty 2\pi r_n = \sum_{n=0}^\infty 2\pi \left(\frac k{1+k} \right)^nr_1 = \frac {2\pi r_1}{1-\frac k{1+k}} = 2\pi r_1(1+k) \\ \sum_{n=1}^\infty A_n & = \sum_{n=1}^\infty \pi r_n^2 = \frac {\pi r_1^2}{1-\left(\frac k{1+k}\right)^2} = \frac {\pi r_1^2(1+k)^2}{1+2k} \\ \implies \frac {\left(\sum_{n=1}^\infty C_n\right)^2}{\sum_{n=1}^\infty A_n} & = \frac {(2\pi r_1(1+k))^2}{\frac {\pi r_1^2(1+k)^2}{1+2k}} = 4\pi (1+2k) \end{aligned}

Let us find k k for O = π 4 \angle O = \dfrac \pi 4 . Then k = l 1 d 1 = l 1 2 r 1 = r 1 csc π 8 r 1 2 r 1 = csc π 8 1 2 = 4 + 2 2 1 2 k= \dfrac {l_1}{d_1} = \dfrac {l_1}{2r_1} = \dfrac {r_1\csc \frac \pi 8 - r_1}{2r_1} = \dfrac {\csc \frac \pi 8 - 1}2 = \dfrac {\sqrt{4+2\sqrt 2}-1}2 . Then

( n = 1 C n ) 2 n = 1 A n = 4 π ( 1 + 2 k ) = 2 π 4 + 2 2 32.8 \frac {\left(\sum_{n=1}^\infty C_n\right)^2}{\sum_{n=1}^\infty A_n} = 4\pi (1+2k) = 2\pi \sqrt{4+2\sqrt 2} \approx \boxed{32.8}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...